2021
DOI: 10.1108/edi-04-2021-0099
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender inequality in education and employment on economic performance in Turkey: evidence from a cointegration approach

Abstract: PurposeThis study aims to empirically examine the impact of gender-based inequalities in both education and employment on economic performance using the dataset of Turkey for the period 1975–2018.Design/methodology/approachThis study employs Johansen cointegration tests to analyze the existence of a long-term relation among variables. Furthermore, dynamic ordinary least squares (DOLS) and fully modified ordinary least squares (FMOLS) estimation methods are performed to determine the long-run coefficients.Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…While, primary and secondary school education enrolment of women negatively affect economic growth. Esen and Seren (2021) studied the impact of gender inequality in education and employment on economic performance in Turkey using Johansen cointegration tests and ordinary least squares estimation methods. The study revealed that there is a long-term relationship between inequality in education and economic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While, primary and secondary school education enrolment of women negatively affect economic growth. Esen and Seren (2021) studied the impact of gender inequality in education and employment on economic performance in Turkey using Johansen cointegration tests and ordinary least squares estimation methods. The study revealed that there is a long-term relationship between inequality in education and economic performance.…”
Section: Literature Reviewmentioning
confidence: 99%